1998
DOI: 10.1111/j.1559-1816.1998.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Application of the Theory of Reasoned Action to Women's Career Behavior1

Abstract: Based on the theory of reasoned action (TRA; Fishbein & Ajzen, 1975), we hypothesized that young women's career intentions would be predicted by their genderrole attitudes and perceptions of their boyfriends' and parents' career-related preferences for them. Career intention was expected to predict future career behavior. The model was tested using longitudinal data from 105 women studied in 1973 and followed up 14 years later in 1987. Data were analyzed using structural equation modeling. Results supported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
0
29
1
5
Order By: Relevance
“…Giles and Rea (1999) found that the same predictors explained around 70% of the variance in intentions to pursue people or action-centered kinds of career, though SN did not make a unique contribution. Vincent, Peplau and Hill (1998) found that both gender-role attitudes and SN Theory of Planned Behavior and Occupational Intentions 6 predicted women's career intentions (PBC was not assessed). Van Hooft et al (2004) found that instrumental and affective attitudes, SN and PBC increased the explained variance in intention to search for jobs from .32 (explained by control variables) to .60, though PBC (in the form of self-efficacy) did not make a unique contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Giles and Rea (1999) found that the same predictors explained around 70% of the variance in intentions to pursue people or action-centered kinds of career, though SN did not make a unique contribution. Vincent, Peplau and Hill (1998) found that both gender-role attitudes and SN Theory of Planned Behavior and Occupational Intentions 6 predicted women's career intentions (PBC was not assessed). Van Hooft et al (2004) found that instrumental and affective attitudes, SN and PBC increased the explained variance in intention to search for jobs from .32 (explained by control variables) to .60, though PBC (in the form of self-efficacy) did not make a unique contribution.…”
Section: Introductionmentioning
confidence: 99%
“…12 Commonly studied factors include attractiveness of job attributes, organizational reputation, labor market conditions, recruiter characteristics, and perceptions of job-person fit. 13 However, until recently, demographic differences were given scant attention, and studies that specifically incorporate a diversity perspective, such as those employing social cognitive career theory 14 and the theory of reasoned action, 15 are relatively new. While many traditional theories ignore demographic differences, some researchers have demonstrated significant differences between groups in terms of job seeking behavior.…”
Section: Career Choice and Demographicsmentioning
confidence: 99%
“…TPB has been employed in many studies that examine decision-making processes, including moral behaviour (Man, 1998;Vallerand et al, 1992), information communication and technology engagement (Siragusa and Dixon, 2009), online shopping intentions (Chuchinprakarn, 2005), and choice of travel mode (Bamberg, Ajzen and Schmidt, 2003). TPB is also useful for predicting behaviours, such as smoking cessation (Norman, Conner and Bell, 1999) and career choice (Vincent, Peplau and Hill, 1998;Zellweger, Sieger and Halter, 2010). TPB has been well-tested in the educational domain and is used to study school choice (Goh, 2007), institutions of higher education (Chen and Zimitat, 2006), business ethics courses (Randall, 1994) and intentions for teaching online public relations courses (Knabe, 2012).…”
Section: Theoretical Framework For the Studymentioning
confidence: 99%